Exploring key factors associated with training quality among elite para-athletes. A qualitative study - Øvstehage, V.; Sandbakk, S. B.; Kocbach, J.; Sandbakk, Ø. (Frontiers in Sports and Active Living, 2025)
Introduction: Despite extensive research on training load characteristics, knowledge about training quality remains sparse. Training quality encompasses two dimensions: quality in the training process and quality in specific training sessions. Elite para-athletes perform high volumes of training, and their training execution may be further influenced by their impairment and sport. No research has explored training quality among elite para-athletes. Therefore, the aim of this study was to qualitatively explore key factors associated with training quality among elite para-athletes across different impairments and sports.